Penerapan Fungsi MSDM Dalam Upaya Meningkatkan Produktivitas Karyawan dalam Menyongsong Revolusi 4.0 - Pradana, Fiqram Iqra; Aqil, Muhammad; S, Ramli (Journal of Management Branding, 2024)
A resilient organization or company can survive all forms of change and the challenges of the times. This research aims to determine the application of human resource management functions in increasing employee productivity in welcoming Revolution 4.0. HRM that runs well will certainly be an advantage for every company and will ultimately improve the performance of its employees. The type of method used in this article is a literature review. The writing of this literature review adopted almost 80% of international and national articles published on various journal provider platforms on an international and national scale that discuss HRM, Productivity and Revolution 4.0. The research results show that implementing HRM functions by utilizing technology appropriately can increase employee productivity. Both managerial functions and operational functions.